Studies of samarium(II) iodide-induced ring openings and donor-acceptor cyclopropanes. - Lund, Elizabeth Anne. (University of Ottawa (Canada), 1994)
Studies based on radical-induced ring openings of halolactones, spirocyclobutanones, and Rh$\sb2$(OAc)$\sb4$-catalyzed reactions of $\alpha$-diazoketones are described. Novel ring openings and subsequent decarboxylations of iodolactone 66 and bromolactone 67 to give diene 78 were found to proceed under SmI$\sb2$/THF/HMPA (4 equiv) conditions. Upon treatment of iodothialactone 63, iodolactone 66 or bromolactone 67 with SmI$\sb2$/THF/HMPA with "reverse addition" it was found that the ring-opened unsaturated acid 79 was obtained in good yield in each case. The unprecedented ring opening reactions of $\alpha$-ketospirocyclobutanes 123 and 124 with SmI$\sb2$ afforded ketones 126 and 127 in 70% and 88% yield, respectively. Dihydrofurans 217 and 224 were prepared from azibenzil (210) and $\alpha$-diazoketone 223, respectively, via Rh$\sb2$(OAc)$\sb4$-catalyzed reactions with ethyl vinyl ether. The structures of 217 and 224 were rigorously established and the former assignments were corrected. These structures (217 and 224) were unamiguously assigned by characterization of the corresponding transketalization products 222 and 226. Preliminary studies towards the preparation of the novel hydrocarbon-soluble Sm(II) complex 88 are presented. An unprecedented Grob-type fragmentation is postulated to explain the formation of benzyl alcohol from the DIBAL reduction of the donor-acceptor cyclopropane 215. Cyclopropyl alcohol 259 was also produced from this reaction. The characterization of 259 established the intermediacy of donor-acceptor cyclopropanes in the production of dihydrofurans 217 and 224, and suggests that this pathway is more general than the literature implies.$\sp*$ ftn$\sp*$Please refer to the dissertation for diagrams.
Keywords: Chemistry, Organic.